2004
DOI: 10.1086/383317
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous Infectious Diseases Associated with Tumor Necrosis Factor Antagonists

Abstract: The relationship between the use of tumor necrosis factor antagonists and onset of granulomatous infection was examined using data collected through the Adverse Event Reporting System of the US Food and Drug Administration for January 1998-September 2002. Granulomatous infections were reported at rates of approximately 239 per 100,000 patients who received infliximab and approximately 74 per 100,000 patients who received etanercept (P<.001). Tuberculosis was the most frequently reported disease, occurring in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
602
4
48

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 890 publications
(676 citation statements)
references
References 23 publications
22
602
4
48
Order By: Relevance
“…However, a systematic review of the FDA Adverse Events Reporting System (AERS) database from January 1998 to September of 2002 showed that granulomatous infections with INF were reported 3.25 times that of ETA and that 72% of INF-associated infections occurred within the first 90 days [87]. Although the incidence of fungal infections after anti-TNF therapy is extremely low and there is no clear indication that any one agent predisposes patients to fungal infections, a number of fungal infections have been reported to the FDA AERS.…”
Section: Adverse Consequences Of Tnfα Blockade Therapies Infectionsmentioning
confidence: 99%
“…However, a systematic review of the FDA Adverse Events Reporting System (AERS) database from January 1998 to September of 2002 showed that granulomatous infections with INF were reported 3.25 times that of ETA and that 72% of INF-associated infections occurred within the first 90 days [87]. Although the incidence of fungal infections after anti-TNF therapy is extremely low and there is no clear indication that any one agent predisposes patients to fungal infections, a number of fungal infections have been reported to the FDA AERS.…”
Section: Adverse Consequences Of Tnfα Blockade Therapies Infectionsmentioning
confidence: 99%
“…Most of these reports were from countries other than the US, and the cases were associated with infliximab. A recent review of this database revealed that TB cases associated with infliximab developed significantly sooner after drug administration than did those associated with etanercept (15). Most of these cases probably represent progression of LTBI to active TB, although the contribution of recent infection to this total is unknown (1).…”
Section: Perspectivementioning
confidence: 99%
“…Sparing T lymphocyte function is the lesson from the human immunodeficiency virus 1 epidemic. When comparing TNF blocking therapies to anakinra treatment, there is a remarkable difference in the number of opportunistic infections between reducing TNF␣ and IL-1 activities (21). In marked contrast, there are hardly any voluntary reports, or findings in controlled trials, of opportunistic infections in rheumatoid arthritis patients treated with anakinra (22), including populations at high risk for reactivation of Mycobacterium tuberculosis infections (23).…”
Section: How Best To Reduce Il-1 Activities: Receptor Antagonism Andmentioning
confidence: 99%